Improving the Productivity of Cross-Generational Relationship Managers in the Banking Sector - Lestari, Dwi Indah; Kurniawan, Bernadi; Perdana, Mirwan Surya; Mahfudz (LifeSciFi, 2024)
This study explores the impact of adaptive education on employee empowerment and productivity among Relationship Managers (RMs) at BRIguna, focusing on differences in learning preferences across generations. Using a qualitative descriptive approach, this study highlights that Generation X, Millennials, and Generation Z have different training preferences, with Generation X preferring formal face-to-face training, while Millennials and Gen Z prefer flexible technology-based learning methods. The results emphasize the importance of adaptive education tailored to individual learning styles, indicating that technology-based training has a positive impact on productivity, especially among generations familiar with technology. Direct observation and thematic analysis suggest that blended learning can bridge generational differences, accommodate diverse preferences, and increase engagement and efficiency in the workplace. In addition, adaptive training that is tailored to employees’ learning preferences increases their sense of being valued and empowered, which positively influences their loyalty and commitment. This study contributes to the literature on adaptive education in multigenerational organizations, particularly in the banking sector, by offering insights into the design of effective training programs to maximize productivity, engagement, and retention across generations. These findings also open opportunities for further research on the role of adaptive education in creating a cohesive, inclusive, and productive work environment amidst generational diversity.